Sustainable Production of Microbial Isoprenoid Derived Advanced Biojet Fuels Using Different Generation Feedstocks: A Review - Walls, Laura Ellen; Rios-Solis, Leonardo (Frontiers in Bioengineering and Biotechnology, 2020)
As the fastest mode of transport, the aircraft is a major driver for globalization and economic growth. The development of alternative advanced liquid fuels is critical to sustainable development within the sector. Such fuels should be compatible with existing infrastructure and derived from second generation feedstocks to avoid competition with food markets. With properties similar to petroleum based fuels, isoprenoid derived compounds such as limonene, bisabolane, farnesane and pinene dimers are of increasing interest as ‘drop-in’ replacement jet fuels. In this review potential isoprenoid derived jet fuels and progress toward their microbial production was discussed in detail. Although substantial advancements have been achieved, the use of first generation feedstocks remains ubiquitous. Lignocellulosic biomass is the most abundant raw material available for biofuel production, however, technological constraints associated with its pretreatment and saccharification hinder its economic feasibility for low-value commodity production. Non-conventional microbes with novel characteristics including cellulolytic bacteria and fungi capable of highly efficient lignocellulose degradation and xylose fermenting oleaginous yeast with enhanced lignin-associated inhibitor tolerance were investigated as alternatives to traditional model hosts. Finally, innovative bioprocessing methods including consolidated bioprocessing and sequential bioreactor approaches, with potential to capitalize on such unique natural capabilities were considered.